Analisis Pertumbuhan lalu Lintas Dan Perkiraan Volume Lalu Lintas Dimasa Mendatang Berdasarkan Volume Lalu Lintas Harian Rata - Rata (Studi Kasus Ruas Jalan Sp. Lago-Sorek / Jalan Lintas Timur - Wahyuni Wahab; Leo Sentosa; Mardani Sebayang (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Road planning techniques need some technical criteria to use as consideration for optimation of planning results to anticipate problems because of road, like social issues or technical issues. One of the criteria necessary planning is value of traffic growth. However, in developing countries including Indonesia, traffic analysis could support planning data with accuracy difficult that adequate. Because of lack of required data, so that difficult to predict future developments. This study aims to analyze value of traffic growth based on value of traffic volume from UR Research Institute survey on Sp. Lago - Sorek street in 2006 until 2013 without traffic volume data in 2008. And also to estimate the future of traffic volume on periods 5 years, 10 years, and 20 years later using value of the traffic growth and regression analysis method. The results show the value of traffic growth on Sp. Lago-Sorek street based on daily traffic volume average are 6.82% of total vehicle (kend/hari) and 4.12% for total vehicle (Smp/hari), traffic volume predicts of total vehicle based on value of traffic growth for year 2018 are 8429 (kend/hari) and 10050 (smp/hari), for year 2023 are 11721 (kend/hari) and 1230 (smp/hari), and for year 2033 are 22666 (kend/hari) and 10513 (smp/hari). Estimated volume of traffic Total Vehicles by regression analysis equation without traffic volume data in 2008 for year 2018 amount to 6915 (kend/hari) and 9239 (smp/hari), for year 2023 amount to 7480 (kend/hari) and 9759 (smp/hari), and for year 2033 amount to 8320 (kend/hari) and 10513 (smp/hari)Keywords: the value of traffic growth, estimate the future of traffic volume, traffic volume.